Department of Veterinary Medicine, Vanbandhu Veterinary College, Navsari Agricultural University, Navsari-396450, Gujarat - Mehta, SA; Patel, RM; Vagh, AA; Mavadiya, SV; Patel, MD; Patel, MD; Vala, JA; Parmar, SM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 145 faecal samples were collected from the dogs suspected for canine parvovirus (CPV) infection over a period of one year from April, 2016 to March, 2017. The faecal samples were screened by HA, Scan Vet Parvo kit and PCR. Out of 145 dog faecal samples screened, 63 samples were positive with an overall prevalence of 43.44 %. Breed wise analysis of data indicated higher prevalence in indigenous breeds (46.67%) than the exotic breeds (42.00%). CPV infection in relation to age was highest (54.05%) in 0-2 months and least (30.43%) in above 4-6 months old dogs. Sex wise analysis revealed the higher prevalence (48.15%) in female dogs than male (40.66%). Month wise prevalence of CPV infection was found highest (65.00%) in February and lowest (12.50%) in June. The prevalence of CPV infection was high (44.03%) in unvaccinated dogs than the vaccinated dogs (36.36%). The findings suggested need of adopting rigorous control and preventive measures against this disease particularly in young dogs.
Keywords: Dog; CPV; Prevalence; Faecal samples; PCR